2017
DOI: 10.1007/s10067-017-3853-9
|View full text |Cite
|
Sign up to set email alerts
|

The 3′-UTR (CA)n microsatellite on CD40LG gene as a possible genetic marker for rheumatoid arthritis in Mexican population: impact on CD40LG mRNA expression

Abstract: The objective of this study was to determine the association of the CD40LG 3'-UTR (CA)n microsatellite with rheumatoid arthritis (RA) and CD40LG mRNA levels in females from western Mexico. A case-control study with 219 RA patients and 175 control subjects (CS) was conducted. Genotyping was performed by polymerase chain reaction (PCR), X test was used to compare genotype and allele frequencies, and odds ratios and 95% confidence intervals were calculated to evaluate the association between RA and the microsatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previous reports have shown that SSR variations located within the 3′ untranslated region (UTR), 5′ UTR, introns, or CDS of a gene affect gene function [3640]. We are concerned about the unintended effects of the 62 differential SSRs on the traits of D62B and DXB.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that SSR variations located within the 3′ untranslated region (UTR), 5′ UTR, introns, or CDS of a gene affect gene function [3640]. We are concerned about the unintended effects of the 62 differential SSRs on the traits of D62B and DXB.…”
Section: Discussionmentioning
confidence: 99%